Analisis Properti Psikometri: Liverpool Stoicism Scale Berbahasa Indonesia pada Mahasiswa Generasi Z (Jurnal Ilmiah Psikologi MIND SET, 2025)
This study aims to evaluate the suitability of the 20-item Liverpool Stoicism Scale (LSS) translated into Indonesian for measuring the unobservable construct of Stoicism among Generation Z undergraduate students (n=325). The questionnaire was distributed online, using Beaton, et al. (2000) cross-cultural adaptation method. Factor analysis was performed using both Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The CFA results indicated factor loadings ranging from 0.120 to 0.477, with a reliability coefficient (α = 0.751) deemed acceptable. However, the EFA results identified only 5 items that loaded onto 2 factors, accounting for 59.199% of the variance, with a low reliability coefficient (α = 0.454). In conclusion, the Indonesian version of the LSS demonstrates weak validity and reliability, thus it does not meet the standards required to measure stoic behavior in Generation Z undergraduate students.